Is It Really a Matter of Simple Dualism? Corticotropin-Releasing Factor Receptors in Body and Mental Health - Janssen, Donny; Kozicz, Tamas (Frontiers in Endocrinology, 2013)
Physiological responses to stress coordinated by the hypothalamo-pituitary-adrenal (HPA-) axis are concerned with maintaining homeostasis in the presence of real or perceived challenges. Regulators of this axis are corticotrophin releasing hormone (CRF) and CRF related neuropeptides, including urocortins (Ucn) 1, 2 and 3. They mediate their actions by binding to CRF receptors (CRFR) 1 and 2, which are located in several stress related brain regions. The prevailing theory has been that the initiation of and the recovery from an elicited stress response is coordinated by two elements, viz. the (mainly) opposing, but well balanced actions of CRFR1 and CRFR2. Such a dualistic view suggests that CRF/CRFR1 controls the initiation of, and urocortins/CRFR2 mediate the recovery from stress to maintain body and mental health. Consequently, failed adaptation to stress can lead to neuropathology, including anxiety and depression. Recent literature, however, challenges such dualistic and complementary actions of CRFR1 and CRFR2, and suggests that stress recruits CRF system components in a brain area and neuron specific manner to promote adaptation as conditions dictate.